The Effect of Location, Promotion, and Price Perception on Clothing Purchase Decisions (Case Study of My Subscriber Store) Bengkulu City - Selvi Andika; Yulius Wahyu Setiadi (Journal of Indonesian Management, 2021)
This study aims to analyze the effect of location, promotion, perceived price on purchasing decisions. This study uses purposive sampling. The sample in this study amounted to 50 respondents. The research method used is quantitative methods. The data collection instrument used a questionnaire. The independent variable is the purchasing decision variable and the dependent variable is location, promotion, and price perception at my favorite clothing store. In this study, the authors used data collection methods by means of observation, interviews and distributing questionnaires or questionnaires. The data that has been collected is processed using test instruments, analysis of respondents' responses, calcic assumption test, multiple linear regression analysis, coefficient of determination (R2) and hypothesis testing. The results showed that the variables of location, promotion, and price perception had a significant effect on the decision to buy clothes in a regular shop in the city of Bengkulu. The results of the t test for the location variable (X1) show the value of t_hit> t_ (α / 2) (3.371> 1.97882) and (sig α = 0.001 <0.050), the promotion variable (X2) shows the value of t_hit> t_ (α / 2 ) (6.352> 1.97882) and (sig α = 0.000 <0.050), the price perception variable (X3) shows the value of t_hit> t_ (α / 2) (3.371> 1.97882) and (sig α = 0.001 <0.050) . The results of the F test, the significant value of F, which is 0.000 less than 0.050 and Fcount is greater than Ftable, the value of Fcount> Ftable, namely (31.736> 1.65685) and (sig α = 0.000 <0.050). From the results of data processing, it can be concluded that all variables of location, promotion, and price perception simultaneously have a significant effect on the dependent variable, namely the purchase decision. Apart from that, from the results of the linear regression test, the equation for the regression is as follows: Y = 1.648 + 0.394 X1 + 0.266 X2 + 0.287X3.